Employee perspectives on decision-making processes in healthcare organization: An insider's view - Gavrilović Nikola; Momirović Stojković Milena; Basara Nada; Lajko Nora (ABC: časopis urgentne medicine)
Introduction: This research analyzes decision-making processes in a primary healthcare institution, with a specific focus on the perspectives of employees within the organization. The contextualization of the study encompasses the importance of examining these processes to enhance efficiency and transparency in decision-making within the healthcare sector. Objective: The research aims to explore and assess the clarity of decision-making frameworks within the organization, with a particular emphasis on the role of top management in business process planning. Establishing these objectives provides the foundation for analyzing employee attitudes and identifying key aspects influencing decision-making processes. Materials and methods: The study was conducted within primary healthcare, involving 67 participants from various departments. A standardized questionnaire with 16 questions was utilized, and data analysis employed descriptive statistical methods through the IBM SPSS program. Results: Results analysis indicates that 50.70% of participants believe there are clearly defined decision-making frameworks, while 61.20% perceive business process planning to be within the purview of top management. Moreover, 34.30% disagree with the assertion that all employees participate in decision-making, and 41.80% confirm that in demanding situations, everyone awaits the designated resolver. Conclusion: The obtained results highlight positive perceptions regarding defined decision-making frameworks and the role of top management in business process planning. However, variations in employee participation in decision-making and challenges in demanding situations have been observed. These findings underscore the need for further improvement in decision-making processes within healthcare organizations, considering employee perspectives.